1966
DOI: 10.1111/j.1476-5381.1966.tb01845.x
|View full text |Cite
|
Sign up to set email alerts
|

THE POSSIBLE ROLE OF ACETYLCHOLINE IN SCHISTOSOMA MANSONI

Abstract: It has been demonstrated that extracts of Schistosoma mansoni contain high acetylcholinesterase and choline acetylase activities (Bueding, 1952). Subsequently, acetylcholine esterase and choline acetylase activities were found by Chance & Mansour (1953) in another trematode, the liver fluke Fasciola hepatica. Furthermore, it has been reported that Fasciola hepatica contains an acetylcholine-like substance and that a variety of cholinomimetic agents exert an inhibitory effect on the muscular activity of this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
2

Year Published

1969
1969
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 15 publications
3
36
0
2
Order By: Relevance
“…The principal physiological role of AChE is believed to be termination of transmission at cholinergic synapses by rapid hydrolysis of the neurotransmitter (ACh) (36). ACh and AChE have been demonstrated to be involved in the motor activity of the schistosome (37)(38)(39)(40)(41). Their presence has been established at several developmental stages of the parasite, including cercaria, schistosomula, and adult worm.…”
Section: Discussionmentioning
confidence: 99%
“…The principal physiological role of AChE is believed to be termination of transmission at cholinergic synapses by rapid hydrolysis of the neurotransmitter (ACh) (36). ACh and AChE have been demonstrated to be involved in the motor activity of the schistosome (37)(38)(39)(40)(41). Their presence has been established at several developmental stages of the parasite, including cercaria, schistosomula, and adult worm.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine-like drugs have been shown to induce flaccid paralysis in the trematode, Schistosoma mansoni (Barker, Bueding & Timms, 1966). Muscarine-like drugs were without activity.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a subsequent return of enzyme activity was associated with a return of the worms to the mesenteric veins. Since there is evidence for a physiological role of acetylcholine in schistosomes (Bueding, 1952;Barker et al, 1966) and since administration of another antischistosomal compound, i.e., p-rosaniline, results in an inhibition of AChE activity of S. mansoni (Bueding et al, 1967), it is possible that AChE inhibition produces functional damage to the worm.…”
Section: Discussionmentioning
confidence: 99%
“…Since many organophosphorus compounds are potent inhibitors of various cholinesterases and since there is evidence that acetylcholine may be a humoral neurotransmitter in Inhbition of schistosme cholinesterases schisto (Somes (3ueding, 1952;Barker, Bueding & Timms, 1966) on schistosome cholinesterases were studied. It was found that differences in the chemotherapeutic activities of metrifonate in human subjects infected with S. haematobiwm, on the one hand, and with S. mansoni on the other, could not be accounted for by differences in the inhibitory potency of metrifonate on the enzymes catalyzing the hydrolysis of acetylcholine in the two species of trematodes.…”
Section: Introductionmentioning
confidence: 99%